Donepezil modulates the endogenous immune response: implications for Alzheimer's disease. (13th June 2016) - Conti, Elisa; Tremolizzo, Lucio; Santarone, Marta Elena; Tironi, Marco; Radice, Isabella; Zoia, Chiara Paola; Aliprandi, Angelo; Salmaggi, Andrea; Dominici, Roberto; Casati, Marco; Appollonio, Ildebrando; Ferrarese, Carlo
Abstract : Objective: Donepezil (DNPZ) is a drug commonly used for Alzheimer's disease (AD) that may favour a T helper 2 phenotype leading to increased naturally occurring auto‐antibodies (NAb) against beta‐amyloid (Aβ). We hypothesized the involvement of the cholinergic receptors [α7‐nicotnic acetylcholine receptor (α7nAChR)] expressed on peripheral blood mononuclear cells (PBMC). Methods: Fifty patients with mild‐to‐moderate AD, DNPZ treated (DNPZ+, n  = 25) or not (DNPZ−, n  = 25), and 25 matched controls were enrolled and PBMC extracted for both in vitro cultures, and real‐time polymerase chain reaction and chromatin immunoprecipitation assay. Plasma samples were also obtained for Aβ and NAb determination. Results: Donepezil increased in vitro the expression of the transcription factor GATA binding protein 3 (GATA3) through α7nAChR, because prevented by the specific antagonist methyllycaconitine. Ex vivo PBMC α7nAChR mRNA expression was increased in both AD groups, while GATA3 expression was not. A significant increase in the GATA3/interleukin 5 promoter association was found in DNPZ+ patients. Finally, DNPZ+ patients showed both significantly higher plasma levels of anti‐Aβ NAb with respect to DNPZ− patients and Aβ 1‐42 with respect to normal controls. Conclusions: Donepezil might modulate a T helper 2 bias via α7nAChR leading to increased expression of NAb. Further studies on the role of the modulation of the immune response against Aβ may pave the way to innovative therapeutic strategies for AD. Copyright © 2016 John Wiley & Sons, Ltd.